A Study on Fandom and Fan Culture: Socioeconomic Implications in the Digital Era - Hermawan, Jasmine Syifa; Margaret Ginting (LATTE: A Journal of Language, Culture, and Technology ISSN 3063-0754, 2024)
The study of fandom and fan culture has grown in significance in the digital age. Fandoms are communities of individuals with shared interests who participate in activities like reading, viewing, and making fan art. Fandom's socioeconomic effects include its contribution to the production and consumption of cultural content as well as its effects on the travel, entertainment, and retail industries. But there are also societal effects like "gatekeeping" and copyright-related legal problems. It also reveals how crucial it is to comprehend the dynamics of power and identity in fandom communities. This study sheds light on issues with intellectual property and social identity as well as shifts in popular culture and media in the digital age. Keywords: Fandom, fan culture, socioeconomics, crowdfunding, social identity.